A new species of Zecicindela Larochelle & Larivière (Coleoptera: Carabidae: Cicindelinae) from the Mackenzie Basin, New Zealand. Issue 1 (2nd January 2018) - Emberson, Rowan M.; Syrett, Pauline; Blakely, Tanya
ABSTRACT: Zecicindela tekapoensis sp. nov. (Coleoptera: Carabidae: Cicindelinae) is described. It is placed in the endemic genus Zecicindela Larochelle & Larivière, even though it is the only known species in the genus with a tridentate labrum. The specimens were found on a very dry, barren terrace surface near the Tekapo River, in the Mackenzie Basin.